The relationship of moral sensitivity and patient safety attitudes with nursing students' perceptions of disclosure of patient safety incidents: A cross-sectional study. - Eunmi Lee (PLoS ONE, 2020)
Disclosure of patient safety incidents is a healthcare management strategy that primarily involves responding after incidents. We investigated the association between nursing students' moral sensitivity, attitudes about patient safety, and perceptions of open disclosure of patient safety incidents in Korea. Data were collected from 407 nursing students at four nursing universities using self-reported moral sensitivity, attitudes about patient safety, and perceptions about open disclosure of patient safety incidents as measures. The data were analyzed using t-test, one-way analysis of variance, and a multiple regression. As moral sensitivity and attitudes about patient safety improved, nursing students' perceptions regarding the open disclosure of patient safety incidents improved significantly. After controlling for gender, grade, and major satisfaction, the effect of changing attitudes about patient safety was greater than that of moral sensitivity for all perceptions of open disclosure. An education and intervention program is needed to improve nursing students' attitudes about patient safety and promote the open disclosure of patient safety incidents during undergraduate training.